The Management skill After Covid-19 crisis and The new normal life by The director and vice director of Lamphun Special Education Center - Homnan, Thanapol; Prasomsuk, Teerapat; Chotigunjara, Thammaros; Yomsoongnern, Junchai (Journal of Buddhist Studies, 2023)
This research article has three objectives: 1) To examine the management skills of administrators in special education institutions in Lamphun province in response to the new normalcy after the COVID-19 crisis. 2) To study the strategies for developing management skills of administrators in special education institutions in Lamphun province in response to the new normalcy after the COVID-19 crisis. 3) To verify the approaches for enhancing the management skills of administrators in special education institutions in Lamphun province in response to the new normalcy after the COVID-19 crisis. Research result found that. 1) The overall Skills of Educational Institution Administrators responding to New Normal after COVID-19 Crisis of Special Education Center of Lamphun Province is at high level. Also, when we consider each part, all of them are high by descending order as follow; Conceptual skill, Technical skill, and Human skill respectively. 2) Developing methods on Skills of Educational Institution Administrators responding to New Normal after COVID-19 Crisis of Special Education Center of Lamphun Province are as below. Administrators should create working system and administrative technics to apply for the operation toward vision. There should be various forms of clients and stakeholders hearing process. Also, there should be an internal communication by a prompt and up-to-date technology. 3) Method examining result on Skills of Educational Institution Administrators responding to New Normal after COVID-19 Crisis found that the correctness, suitability, probability and utility are 100 percent.